Service Quality in the School of Management, USM: Perceptions of Students in Pursuit of MBA - Isahak Merican, Farah Merican (2007)
In many countries and many cultures, the issue of service quality is firmly on the agenda for higher education institutions. Universities and faculties strive to provide high quality services because they need to compete for their students. Measuring the quality of their services is therefore an important task.